Evaluation of pathogenicity and antifungal resistance of frequently occurred Aspergillus and Fusarium species in swimming pools in selected hotels in Ekiti state - Olalekan Adeola , Pius; Moses David , Oluwole; Adeoye Oluwole , Olusola (International Journal of Basic and Applied Sciences, 2024)
Background: Swimming pools have been reported as critical fungal reservoirs. This study was designed to investigate fungal populations in swimming pools as well as detect the presence of virulence factors in the recovered isolates. Methods: Estimation of the mycobiota in the swimming pools sampled was done and isolates recovered were identified using colonial, morphology and molecular methods. Also, virulence factors: lipase, keratinase, laccase, hydrophobicity and biofilm formation were also determined using standard methods while antifungal susceptibility was done using clinically approved methods. Also, the presence of metalloprotease and protease gene was detected using PCR. Results: Out of the 75 samples, 47 showed fungal growth, with an isolation rate of 25.5%, 34.0%, and 40.4% from the surface, bottom, and edges of the pools respectively. Six fungi species were isolated viz: Candida tropicalis, Aspergillus flavus, Aspergillus niger, Fusarium oxysporum, and Fusarium verticilloides. C. tropicalis had the highest isolation rate at 41.7%. The fungi possessed virulence factors, with keratinase and lipase being the most common. All isolates were resistant to itraconazole, while none were resistant to fluconazole. The metalloprotease gene was detected in A. flavus, F. verticilliodes, and F. oxysporum. Conclusion: Our study revealed that the fungi recovered from the swimming pool possessed virulence factors that can enhance their infectivity.